Performance of new pp65-IGRA for the quantification of HCMV-specific CD4+ T-cell response in healthy subjects and in solid organ transplant recipients - Mele, Dalila; Zavaglio, Federica; Bergami, Federica; Gregorini, Marilena; Briganti, Domenica Federica; Pellegrini, Carlo; Comolli, Giuditta; Cassaniti, Irene; Lilleri, Daniele; Baldanti, Fausto (Frontiers in Immunology, 2025)
Immune control of human cytomegalovirus (HCMV) replication is critical in bone marrow and solid organ transplant recipients, where uncontrolled replication can lead to high mortality. Current commercial immune monitoring tools have several limitations, such as a lack of appropriate test cutoff values and the inability to characterise antigen-specific T cells. The main aim of our study was to develop a new interferon-γ (IFN-γ) release assay (IGRA), easy to use, to quantify and characterise the HCMV-specific T-cell response (pp65-IGRA). Secondary analyses included an evaluation of the performance of pp65-IGRA to assess whether its specificity and sensitivity were equal to or greater than those of the intracellular cytokine staining (ICS) and enzyme-linked immunospot (ELISpot) assays. In the study, 76 immunocompetent donors and nine solid organ transplant recipients were enrolled. Blood samples or peripheral blood mononuclear cells were stimulated with HCMV pp65-recombinant protein or with a complete pool of overlapping pp65 peptides. IFN-γ production was analysed by enzyme-linked immunoassay, ELISpot assays, and flow cytometry. For each assay, appropriate cutoff values were calculated. Our data demonstrate the suitability of pp65-IGRA for the quantification of HCMV-specific CD4+ T-cell responses and may support its use in routine clinical practice to improve the management of immunocompromised patients.